Enhancement of Ferromagnetic and Ferroelectric Properties in Codoped BiFeO3 - Chatterjee, B.; Kevin, H.; Dwivedi, G.D.; Yang, H.D.; Chatterjee, S.; Ghosh, A.K. (Asian Journal of Chemistry, 2011)
Co-doped insulating Bi0.8La0.2Fe1-xMnxO3, (x = 0, 0.1) ceramics were prepared by conventional solid state reaction method. The XRD study shows that 20 % substitution of La ions changes the structure from rhombohedral (space group R3c) that of BaFeO3 to the orthorhombic (C222) for Bi0.8La0.2FeO3 (BLFO). For further substitution of Mn-ions in Fe-site no structural change occurs. From DTA and TGA study, it is observed that magnetic transition temperature (Tm) decreases appreciably whereas ferroelectric transition temperature (TC) does not affect much with the increase of Mn-concentration. The magnetization-magnetic field measurements show that increase of magnetization for co-doping of La and Mn in Bi0.8FeO3 is due to the destruction of the spin cycloid structure in it and the introduction of the mixed valance state. P-E measurement shows the ferroelectric nature of the sample.